An exploration of how female Filipino K-Pop fans negotiate their cultural beliefs on femininity through female K-Pop idols - Papa, Alessandra Nicole G.
Femininity is a cultural construct (Elfving-Hwang, 2010), which manifests in the different ideas of femininity in Korean and Filipino cultures. Through the global phenomenon of K-pop, Filipino fans experience the aspects of these two cultures simultaneously. This thesis examines how Filipino K-pop fans negotiate their cultural beliefs on femininity through female K-pop idols. It describes Filipino K-pop fans’ motivations and reasons for liking female K-pop idols and examines how Filipino K-pop fans understand the concept of Korean femininity through these idols. To answer the research question, the researcher adopted Schrøder’s multidimensional model integrated with concepts of femininity, cultural hybridity, and participatory culture. The researcher employed a qualitative approach and used thematic analysis to analyze data gathered from seven participants through an interview. It was found that fans’ personal beliefs manifest in their motivations in liking idols. Fans’ personal beliefs also influence how they comprehend idols’ portrayal of femininity, along with the femininity that they wish to see from idols. Thus, fans’ beliefs play a huge role in how they negotiate their ideas on femininity through idols.